The Feasibility study of himalayan pink salt in laboratory procedure focusing on serial dilution and red blood blood cell suspension - Bambalan, Jean Anne Nicolle H.; Ferrer, Smig C.; Manipol, April Aaron N.; Sioco, Jairah Anne B. (Manila : National University, 2024)
This study aims to assess the feasibility of using a Himalayan pink salt solution in these laboratory procedures.
Chapter 1. Introduction -- Chapter 2. Review of related literature -- Chapter 3. Methodology -- Chapter 4. Presentation, Analysis and Interpretation -- Chapter 5. Summary of Findings, Conclusions and Recommendation -- References.
Includes bibliographical references.